An exploration of the reasons women give for choosing legal termination of pregnancy at Soshanguve Community Health Centre, Pretoria, South Africa - Carrien Steyn; Indiran Govender; John Velaphi Ndimande (South African Family Practice)
Background: Termination of pregnancy (TOP) is one of the most commonly performed gynaecological procedures in the world and was legalised in South Africa in 1996 with the passing of the Choice on Termination of Pregnancy Act, 1996 (Act No. 29 of 1996). Utilisation of the TOP service increased significantly after the promulgation of the Act, to the extent that 7% of pregnant women in South Africa chose to terminate their pregnancies legally in 2012. Worldwide, women most commonly state their reasons for choosing TOP as a desire to stop or postpone childbearing. Although several international studies have been done in this regard, the reasons for women requesting legalised TOP in South Africa have not been explored in depth. Methods: A qualitative study using the case-study approach and involving one-on-one open interviews with participants was done at the TOP Clinic at Soshanguve Clinic 3 with the aim of gaining more insight into this issue. Results: The following themes emerged from the interviews: formal education not completed, financial difficulties, contraceptive failure, wrong timing, reasons relating to the existing family; and problems relating to the partner. Conclusion: This study also gave insight into the complex personal and social contexts within which women make the decision to terminate their pregnancy, and the thoughtfulness with which they make their decisions.